Histone modifications and metabolic reprogramming in tumor-associated macrophages: a potential target of tumor immunotherapy - Xu, Yiting; Zhang, Han; Nie, Dengyun (Frontiers in Immunology, 2025)
Histone modifications, including methylation, acetylation, lactylation, phosphorylation, ubiquitination, SUMOylation, ADP-ribosylation, and crotonylation, critically regulate tumor-associated macrophages (TAMs) polarization by modulating gene expression and functional states. Reprogramming TAMs from M2 to M1 phenotypes through epigenetic targeting has emerged as a promising strategy to enhance anti-tumor immunity and improve the efficacy of cancer immunotherapy. This review explores the role of histone modifications in TAM biology, their interplay with metabolic reprogramming, and the opportunities and challenges in developing epigenetic-based therapies to advance cancer immunotherapy.